The Importance of Social Capital in Developing Students' Literacy Skills in Elementary Schools - Wibowo, Ari; Gularso, Dhiniaty; Purwaningsih, Okti (Universitas Pendidikan Ganesha, 2024)
Instilling literacy skills from an early age has a significant impact in forming the basis of a child's development and leads to strong literacy skills in the future. This research aims to analyze the role of social capital in growing student literacy in elementary schools. The method used in this research is library research. The procedures for researching this literature are (a) formulating the problem, (b) collecting data, (c) evaluating the suitability of the data, (d) analyzing and interpreting relevant data, and (e) organizing and presenting the results. Recognition of the important role of social capital in fostering literacy skills from an early age in elementary school is key to ensuring that future generations have a strong literacy foundation that will help them succeed in their education and everyday life. This article explains the importance of social capital in fostering literacy skills from an early age through the role of family, school and community. The results of this research support that investing in social capital for students' literacy education has a long-term impact in improving their literacy skills in the future.